2014
DOI: 10.5194/bg-11-3477-2014
|View full text |Cite
|
Sign up to set email alerts
|

Can a bog drained for forestry be a stronger carbon sink than a natural bog forest?

Abstract: Abstract. This study compares the CO 2 exchange of a natural bog forest, and of a bog drained for forestry in the pre-Alpine region of southern Germany. The sites are separated by only 10 km, they share the same soil formation history and are exposed to the same climate and weather conditions. In contrast, they differ in land use history: at the Schechenfilz site a natural bog-pine forest (Pinus mugo ssp. rotundata) grows on an undisturbed, about 5 m thick peat layer; at Mooseurach a planted spruce forest (Pic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 71 publications
1
34
0
Order By: Relevance
“…Similar magnitudes of −49 and −61 g C m −2 yr −1 were reported for an Irish blanket bog by Sottocornola and Kiely []. Hommeltenberg et al [] determined −53 ± 28 g C m −2 yr −1 and −73 ± 38 g C m −2 yr −1 for a near‐natural forested bog in Southern Germany. NEE ranging from 10 to −76 g C m −2 yr −1 dependent on water availability and snow cover was detected at a cool‐temperate bog in Canada [ Lafleur et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar magnitudes of −49 and −61 g C m −2 yr −1 were reported for an Irish blanket bog by Sottocornola and Kiely []. Hommeltenberg et al [] determined −53 ± 28 g C m −2 yr −1 and −73 ± 38 g C m −2 yr −1 for a near‐natural forested bog in Southern Germany. NEE ranging from 10 to −76 g C m −2 yr −1 dependent on water availability and snow cover was detected at a cool‐temperate bog in Canada [ Lafleur et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, the benefits of drainage on forest productivity are evident; it results in a better tree growth Zalitis & Indriksons, 2009). On the other hand, there may be negative consequences to soil carbon storage (Simola, Pitkänen, & Turunen, 2012;Pitkänen, 2013;Hommeltenberg et al, 2014). On the contrary, some authors have found that carbon stock in forest organic soils can remain stable or even continue to increase after drainage (Minkkinen & Laine, 1998b).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main drivers determining, whether forest organic soil will be carbon source or sink after drainage, is climatic variables. In the boreal vegetation zone drained organic soils in forest often continue to act as a sink (Minkkinen & Laine, 1998b Hommeltenberg et al, 2014). In some cases, emissions from soil can be large enough to turn the whole drained forest ecosystem into CO 2 emitter, especially in the long term (Hommeltenberg et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous studies of NEE measurements in peatlands by the EC technique but they are mostly restricted to boreal ( Cai et al, ), subarctic ( Aurela et al, ) or forest ecosystems ( Dunn et al, ; Hommeltenberg et al, ) and often focus on (near‐) natural site conditions ( Lafleur et al, ). Only few EC measurements of NEE on temperate agricultural utilized or rewetted peatlands are currently available from the Netherlands ( Hendriks et al, ; Jacobs et al, ; Veenendaal et al, ; Parmentier et al., ).…”
Section: Introductionmentioning
confidence: 99%